Persisting anorectal dysfunction after rectal cancer surgery. (November 2013) - Maris, A.; Penninckx, F.; Devreese, A. M.; Staes, F.; Moons, P.; Van, E.; Haustermans, K.; D'Hoore, A.
Abstract Aim Sphincter‐saving rectal cancer management affects anorectal function. This study evaluated persisting anorectal dysfunction and its impact on patients' well‐being. Method Seventy‐nine patients with a follow‐up of 12–37 (median 22) months and 79 age‐ and sex‐matched control subjects completed questionnaires. Results The median number of diurnal bowel movements was three in patients and one in controls (P < 0.0001). Nocturnal defaecation occurred in 53% of patients. The median Vaizey score was 8 in patients and 4 in controls (P < 0.0001). Urgency without incontinence was reported by 47% of patients and 49% of controls (P = 0.873), soiling by 28% of patients and 3% of controls (P < 0.0001), incontinence for flatus by 73% of patients and 49% of controls (P = 0.0019), and incontinence for solid stools by 16% of patients and 4% of controls (P = 0.0153). Incontinence of liquid stools occurred in 17 of 20 patients and in one of five controls who had liquid stools (P = 0.0123). Incontinence for gas, liquid or solid stool occurred once or more weekly in 47%, 19% and 6% of patients respectively. Evacuation difficulties were reported by 98% of patients, but also by 77% of controls. Neoadjuvant radio(chemo)therapy adversely affected defaecation frequency and continence. Incontinence was associated with severe discomfort in 50% of patients, severe anxiety in 40% and severe embarrassment in 48%. Conclusion Anorectal dysfunction is a frequent problem after management of rectal cancer with an impact on the well‐being of patients.